Strategi dan Metode Pembelajaran dalam Pendidikan Agama Islam: Kajian Literatur Konsep, Prinsip Pedagogis, dan Implementasi Kontemporer - Yana, Erli; Andrini, Mike; Syafe’i, Imam; Hadiati, Eti; Rahmatika, Ratu Vina (Paedagogie, 2026)
This study aims to comprehensively analyze the concepts of teaching strategies and methods in Islamic Religious Education (PAI), including the underlying pedagogical principles and the implementation of contemporary methods relevant to students’ needs. The research employs a qualitative library research approach. Data were collected through document studies of books, journal articles, and academic publications, then analyzed using content analysis to examine effective concepts, principles, and methods in PAI. The findings indicate that PAI teaching strategies integrating cognitive, affective, and psychomotor domains, while positioning students as active subjects, align with modern educational theories, particularly constructivism and humanism. The application of pedagogical principles such as exemplarity, habituation, participatory learning, and relevance strengthens the internalization of Islamic values and the effectiveness of learning. Furthermore, contemporary methods, including discussions, problem-based learning, project-based learning, and the use of digital technology, enhance motivation, engagement, and material relevance. Despite challenges related to teacher competence and facilities, the integration of classical Islamic pedagogical principles with modern teaching methods makes PAI not only a means of knowledge transfer but also a medium for character building and 21st-century competency development. The study concludes that strengthening teacher capacity, developing adaptive curricula, and providing adequate learning facilities are essential to achieving the holistic goals of Islamic education.